Dynamic scheduling of multimedia requests in client/server environments - Guan, Huan Ci. (2008)
Scheduling real-time multimedia data in a client-server architecture is a natural approach to support advanced multimedia applications. Due to the limitations existing in network systems and varying request generated by numerous users, scheduling of multimedia data for synchronized delivery over the network with limited resources and quality of service is identified as a complex problem. In this thesis, we discuss some proposed methods to handle these limitations. Many of the existing dynamic algorithm for scheduling real-time application ignore the direct effect of factors, such as when scheduling is performed and the scheduling duration. We propose an algorithm that employ novel, on-line optimization techniques to dynamically schedule a set of sporadic real-time multimedia requests. This algorithm accounts for the scheduling cost and its effect on the ability to meet deadlines. We evaluate this technique by comparing its performance with the performance of a landmark dynamic algorithm. The results show that our proposed algorithm performs better in terms of deadline compliance and scalability as the networking resources increase.